Down-Regulation of Collagen Hydroxylation in Colorectal Liver Metastasis - van Huizen, Nick A.; Burgers, Peter C.; van Rosmalen, Joost; Doukas, Michail; IJzermans, Jan N. M.; Luider, Theo M. (Frontiers in Oncology, 2020)
Collagen is significantly upregulated in colorectal liver metastasis (CRLM) compared to liver tissue. Expression levels of specific collagen types in CRLM resemble those in colorectal cancer (CRC) and colon tissue. We investigated whether the collagen hydroxylation pattern from the primary tumor also migrates with the metastatic tumor. The degree of collagen alpha-1(I) hydroxylation in colon, CRC, liver, and CRLM tissue of the same individuals (n = 14) was studied with mass spectrometry. The degree of hydroxylation was investigated in 36 collagen alpha-1(I) peptides, covering 54% of the triple helical region. The degree of hydroxylation in liver tissue was similar to that in colon tissue. The overall degree of hydroxylation was significantly lower (9 ± 14%) in CRC tissue and also significantly lower (12 ± 22%) in CRLM tissue compared to colon. Furthermore, eleven peptides with a specific number of hydroxylations are significantly different between CRLM and liver tissue; these peptides could be candidates for the detection of CRLM. For one of these eleven peptides, a matching naturally occurring peptide in urine has been identified as being significantly different between patients suffering from CRLM and healthy controls. The hydroxylation pattern in CRLM resembles partly the pattern in liver, primary colorectal cancer and colon.